Peran Guru Pendidikan Agama Islam Dalam Membentuk Karakter Peserta Didik di Kelas VII MTs Al Muhsin Metro Tahun Pelajaran 2022/2023 - Suratno (UNISAN JURNAL, 2023)
The role of Islamic Religious Education (PAI) teachers in shaping the character of students in class VII MTs Al Muhsin Metro has an important role in shaping a person’s morals and ethics, as well as forming good attitudes and behavior. In this discussion, the background of the importance of Islamic religious education is described in shaping the character of students and the important role of Islamic religious education teachers in Islamic religious education. In addition, it also discusses the concept of character and the influence of Islam in shaping the character of students. This study proposes a formulation of the problem which includes the role of the PAI teacher in shaping the character of students, the strategies or methods used, the obstacles encountered, and the efforts that can be made to enhance the role of the PAI teacher in shaping the character of students. With this understanding, it is hoped that a healthy, ethical and moral learning environment can be created in class VII MTs Al Muhsin Metro.